Financial markets and institutions : a European perspectiv - Haan, Jakob de; Schoenmaker, Dirk; Wierts, Peter J. (Cambridge : Cambridge University Press, 2020)
Written for undergraduate and graduate students of finance, economics and business, the fourth edition of Financial Markets and Institutions provides a fresh analysis of the European financial system. Combining theory, data and policy, this successful textbook examines and explains financial markets, financial infrastructures, financial institutions, and the challenges of financial supervision and competition policy. The fourth edition features not only greater discussion of the financial and euro crises and post-crisis reforms, but also new market developments like FinTech, blockchain, cryptocurrencies and shadow banking. On the policy side, new material covers unconventional monetary policies, the Banking Union, the Capital Markets Union, Brexit, the Basel III capital adequacy framework for banking supervision and macroprudential policies. The new edition also features wider international coverage, with greater emphasis on comparisons with countries outside the European Union, including the United States, China and Japan.
Title from publisher's bibliographic system (viewed on 04 May 2020).
Keywords: elektronické knihy; electronic books; Financial institutions -- Europe; Europe -- Economic policy; Europe -- Economic integration